Ankle and foot function in female athletes involved in in-water and dry-land sporting activities - Chatziilias, V. A.; Mandalidis, D. G. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: The stability and mobility of the ankle and foot joints are thought to be improved by cross-training, i.e., transferring the beneficial effects acquired from performing one sporting activity to those required to perform another. This study aimed to investigate the effect of long-term participation with in-water and dry-land sports activities (IWSA, DLSA) on ankle and foot function. METHODS: The study sample consisted of 28 healthy competitive female athletes involved in IWSA (N.=14) and DLSA (N.=14) for <8 years, as well as 15 females not involved in sporting activities (NISA). The isometric strength of the ankle dorsi flexors (ADF), plantar flexors (APF), and subtalar invertors and evertors (SIN, SEV), the ankle dorsi and plantar flexion, and subtalar/forefoot inversion and eversion passive range of motion (ROM), and the static and dynamic balance were assessed in each participant`s supportive lower limb. RESULTS: IWSA athletes demonstrated significantly greater isometric strength in ADF (P<0.01), SIN (P<0.01), and SEV (P<0.05) compared to DLSA athletes and in ADF (P<0.001), SIN (P<0.01) and SEV (P<0.05) compared to NISA individuals with differences between DLSA athletes and NISA individuals being not significant. Between-groups differences on isometric APF strength, passive ROM of the ankle and foot joints, and postural balance were not significant. CONCLUSIONS: DLSA athletes could benefit from long-term participation with IWSA, at least in terms of increasing isometric strength of the ankle and foot stabilizers, as their function does not appear to improve after long-term participation with the sports of their choice, at least compared to NISA individuals.